Enforcement of constitutional rights through constitutional complaint as an embodiment of the law state - Bawembang, Nopesius; Wowor, Karel (Universitas Wiralodra, 2023)
Indonesia is a constitutional state which is based on the constitution as the Constitution of the State. The constitution must take precedence and all actions or regulations originating from authorities delegated by the constitution must not conflict with the constitutional rights of citizens and the constitution itself. The data in this study used secondary data from various sources of literature such as books, laws, literature, and journals. One of the principles of a rule of law is government based on law, which ensures that every state activity has a clear legal basis. The mechanism for reviewing legal regulations, especially constitutional review, prevents actions or decisions that violate the constitutional rights of citizens. Constitutional review is a concept that emerged as a result of the development of modern ideas about a system of government based on a rule of law, separation of powers, and the protection and promotion of human rights. Constitutional review is a legal umbrella to protect citizens from actions or regulations that violate their fundamental rights.